A model for transaction management in mobile databases - Abdul Mehdi, Ziyad; Mamat, Ali; Ibrahim, Hamidah; Mat Deris, Mustafa (2010)
The evolution of mobile computing devices and wireless networks has created a new mobile computing environment. Users equipped with a mobile host can access, retrieve, and process information while in mobility. Laptops become more powerful data processing elements. Traditional transaction model has moved forwarding to mobile transaction. This paper proposed the model with the aims at solving the stated issues. A key requirement in such an environment is to support frequent disconnection of mobile database. Transaction management models for databases, in particular the centralized databases, has long been established. Due to the nature of mobile computers, the traditional transaction management models are no longer appropriate. This paper present a model that implements this framework in an asynchronous and synchronous system.